Strategi Digital Marketing Untuk Meningkatkan Branding Produk Dalam Pengembangan UMKM Bintang Lestari Pada Kelurahan Karangtengah - Alfina Rahma Nazilal Mubarok; Maharani Ikaningtyas (Universitas Katolik Widya Karya Malang, 2023)
The existence of MSMEs in Indonesia is taken into account, because they contribute greatly to economic growth. The MSME sector is one of the main pillars of Indonesia's economic fundamentals. With the development of digitalization, MSMEs will make the digital economy in Indonesia in 2025 the largest in Southeast Asia. Even so, there are obstacles faced by MSMEs, namely the need to strengthen digital literacy education and strengthen human resources for MSME business actors. The problem that is experienced or faced by SMEs is that online marketing education is still low. Like the UMKM Bintang Lestari in Karangtengah Village, Blitar City. Therefore, students and the 32 Thematic Community Service Groups designed strategies and program plans to help improve MSME product branding. The method used in carrying out activities is a qualitative method by means of observation, discussion, documentation and interviews with the UMKM. The results of the activities also have a positive impact, MSMEs can increase sales and marketing and have good product branding in the eyes of the public.